On local strength of a spherical vessel with pits distributed along the equator (Fracture and Structural Integrity, 2022)
The effect of multiple shallow corrosion pits on the strength of a spherical vessel subjected to internal pressure is studied. The pits are considered both randomly and evenly distributed along the equator on the outer surface of the vessel. The dependencies of the stress concentration factor on the number of the pits are compared for linearly elastic and elastic-plastic material with hardening. The behavior of the vessels made of elastic and elastoplastic materials turned out to be qualitatively different. The approximation of periodic pits arrangement is discussed.
Keywords: Pitting corrosion; Surface defects; Spherical shell; Pressure vessel